Navigating Communication: The Challenges and Opportunities for Community Leadership in Indonesia - Anggraeni, Ngurah Ayu Dian; Sasono, Eko; Sopi, Sopi; Mas'ud, Fuad (Management Analysis Journal, 2024)
This research explains community leadership's dynamics in improving communication quality within Indigenous communities.  A quantitative approach is used.  Data was collected through questionnaires in several indigenous communities in Indonesia and analyzed.  The findings show that community leadership faces the challenge of combining modern principles with traditional values to create quality communication.  This research highlights the importance of technological and educational support in strengthening leadership capacity.  The contribution of this research is in the development of community leadership theory.  Further research recommendations include the involvement and impact of technology in community communication.  These findings will guide community leaders and policymakers in creating more inclusive and responsive strategies to meet needs.